The Effect of Muslim Community Acceptance of Sexual Consent on the Effectiveness of the Minister of Education, Culture, Research and Technology Regulation Number 30 of 2021 - Alfath, Tahegga Primananda; Rahmawati, Winda; Wulandari, Safira; Prehatiningsih, Febry Dwi; Muharatulloh, Edshafa (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
This study aims to analyze the effect of Muslim community acceptance on the effectiveness of the Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 (Permendikbudristek No. 30 of 2021). The presence of the phrase